Development of a specific highly sensitive method for the determination of diclofenac sodium in atmospheric air taking into account the characteristics of microconcentrations of the active substance (Environment & Health, 2023)
Objective: to develop a specific, highly sensitive method for determining the concentration of sodium diclofenac in atmospheric air, taking into account the peculiarities of microconcentrations of the active substance.Materials and methods: Air sampling was carried out using a TYPHOON-S4 electric aspirator for 30 minutes at a speed of 20 l/min. The test to determine the concentration of sodium diclofenac in air was carried out by concentrating the analytical sample (aerosol of sodium diclofenac in water) by the method of solid-phase extraction, using Oasis MCX 6cc (150 mg) LP Extraction Cartridges, after which desorption was carried out with solvent - methanol. The obtained samples were analyzed by the method of high-performance liquid chromatography using a Dionex Ultimate 3000 chromatograph with a diode-matrix detector. The sensitivity of the method reaches ng/ml. It is shown that the concentration of the substance determined in the air is within (2-200 μg/m3).The results: As part of the work, a specific, highly sensitive method for determining the concentration of sodium diclofenac in the air was developed and testing was carried out by determining the concentration of sodium diclofenac in the air of the working area of the pharmaceutical enterprise «Lubnifarm» during certain analytical operations (pouring, weighing the substance, crushing tablets containing the active pharmaceutical ingredient under analysis, homogenization).The linear dependence of the diclofenac sodium peak area on the concentration of the substance in the solution (0.025-10 μg/ml) has been proven. The analysis showed that the volatile microparticles of the diclofenac sodium substance are exposed to air deposition, and as a result, a certain amount of this API penetrates into the analyzed samples of other drugs nearby. This fact can lead to obtaining unreliable results during the control of the quality and safety of medicinal products, which can have negative consequences for preserving the health of the population when using medicinal products of inadequate quality.Conclusions: Based on the results of the research, it was established that the developed technique is highly sensitive and will allow determination of nano- and micro-concentrations of sodium diclofenac in atmospheric air.
Keywords: nonsteroidal anti-inflammatory drugs; sodium diclofenac; quality control of drugs; solid phase extraction; air; safety